Pendampingan Upgrade CMS dan Pelatihan Pengoperasian CMS Sekolahku.web.id pada SMP N 2 Karanganyar Demak - Susanti, Nanik; Irawan, Yudie; Muzid, Syafiul; Handayani, Putri Kurnia; Supriyati, Endang (Universitas Muria Kudus, 2024)
The use of school websites as a means of supporting the teaching and learning process as well as promotional media is still very necessary, considering that teachers and students are able to easily access materials and teaching materials without being limited by place and time. So that the student learning process is more flexible and can be done at any time. The use of websites and social media can encourage the effectiveness of the learning and teaching process in schools. So the process of providing materials and teaching materials by teachers needs to be maintained. The existence of the official website at SMP N 2 Karanganyar Demak has supported the online learning process, especially during the Covid-19 pandemic, apart from being an information service and promotional tool. However, currently the official website of SMP N 2 Karanganyar Demak is experiencing problems in development. Therefore, it is necessary to increase the capacity of the official website by replacing the Balitbang CMS with the Sekolahku.web.id CMS which has currently been developed and used by many schools in the archipelago. CMS Sekolahku.web.id has more features and is more flexible in its management.